2020
DOI: 10.1111/ddg.14013
|View full text |Cite
|
Sign up to set email alerts
|

S2k guidelines for the diagnosis and treatment of herpes zoster and postherpetic neuralgia

Abstract: The present guidelines are aimed at residents and board-certified specialists in the fields of dermatology, ophthalmology, ENT, pediatrics, neurology, virology, infectious diseases, anesthesiology, general medicine and any other medical specialties involved in the management of patients with herpes zoster. They are also intended as a guide for policymakers and health insurance funds. The guidelines were developed by dermatologists, virologists, ophthalmologists, ENT physicians, neurologists, pediatricians and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0
41

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(123 citation statements)
references
References 0 publications
0
82
0
41
Order By: Relevance
“…Following the latest S2k guidelines, lidocaine patches are recommended as second-line treatment for postherpetic neuralgia. 41 Some evidence has indicated that lidocaine could affect the release of pro-inflammatory and anti-inflammatory cytokines 42,43 and inhibit peripheral and central sensitization, 44 resulting in analgesic effects. 45 To make our interventions as comparable as possible, all patients received local injection therapies to increase adherence to treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the latest S2k guidelines, lidocaine patches are recommended as second-line treatment for postherpetic neuralgia. 41 Some evidence has indicated that lidocaine could affect the release of pro-inflammatory and anti-inflammatory cytokines 42,43 and inhibit peripheral and central sensitization, 44 resulting in analgesic effects. 45 To make our interventions as comparable as possible, all patients received local injection therapies to increase adherence to treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Topical therapy with lidocaine is effective and well supported by evidence. Following the latest S2k guidelines, lidocaine patches are recommended as second‐line treatment for postherpetic neuralgia 41 . Some evidence has indicated that lidocaine could affect the release of pro‐inflammatory and anti‐inflammatory cytokines 42,43 and inhibit peripheral and central sensitization, 44 resulting in analgesic effects 45 .…”
Section: Discussionmentioning
confidence: 99%
“…While most patients' symptoms settle down within a week with only simple analgesia, others might need antiviral medications like acyclovir, valacyclovir, famciclovir, and brivudine [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although certain patients have a certain tendency to self-heal, PHN can develop in case the virus in the body is not cleared in time and the pain in the affected area lasts for more than 3 months. Its severity usually depends on the presence of pain before the formation of the rash, the severity of the rash, the sex, age, and impaired immune function [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a lack of effective treatment is present, which increases the social medical and family burden 11 . At present, the clinical treatment 12 of PHN is mainly divided into the two following categories: drugs 10,13,14 and surgery 15,16 . When the application of drugs is ineffective or the side effects caused are unbearable, surgery is considered 16 .…”
Section: Introductionmentioning
confidence: 99%